Knowledge management and monitoring of Farmer FIRST Programme through FFP Portal - PAL, SOUMEN; KUMAR, MUKESH; BHARADWAJ, ANSHU; JAIN, RAJNI; KUMAR, SHIV; KUMAR, ARUNA T; GUPTA, CHETNA; RAMA, RAMA (The Indian Journal of Agricultural Sciences, 2021)
The Farmer FIRST (Farm, Innovations, Resources, Science and Technology) Programme (FFP) aims at enriching Farmers' Scientist interface, technology assemblage, application and feedback, partnership and institutional building and content mobilization. This programme has been initiated since October, 2016 to provide a platform to farmers and scientists for creating linkages, capacity development, technology adaptation and application, on-site input management, feedback and institution building. Presently fifty-two (52) projects are running in various ICAR Institutes and Agricultural Universities for implementing the FFP. Farmer FIRST is an opportunity for the researchers, extension professionals and farmers to work together and find appropriate ways through assessing different solutions. A lot of information and knowledge is being generated through 52 FFP projects on different aspects like resource management, climate resilient agriculture, production management including storage, market, supply chains, value chains, innovation systems etc. To manage this information and knowledge, a FFP portal (https://ffp.icar.gov.in/) has been developed during 2017-20 at ICAR Indian Agricultural Statistics Research Institute, and hosted in ICAR Data Center placed at ICAR-IASRI, New Delhi. The portal is developed using .NET framework and it is web responsive. It is a single window platform which provides basic and detailed information with respect to all FFP projects. The portal facilitates the lead centers of the respective projects to update and upload all types of related information so that the knowledge generated in FFP can be disseminated to the farming community. Agricultural Technology Application Research Institute (ATARI) and Agricultural Extension Division of ICAR monitor the project activities and progress under this programme through this portal.